IMPROVEMENT OF POLYACRYLONITRILE FIBER TO REDUCE FLAMMABILITY USING FIRE PROTECTION SYSTEMS - Tursunov Dilshodbek Muhamadbekovich (Western European Studies, 2023)
Today, synthetic fabrics and fabrics made of both natural and artificial fibres compete successfully in the textile and clothing industry. Chemical fibres have several specific properties that surpass the properties of natural fibres (heat resistance, abrasion resistance, durability, elasticity, etc.), which makes them indispensable in many industries. This article discusses the issues of improving polyacrylonitrile fibre to reduce flammability using fire protection systems
Keywords: fibre; natural and artificial fibres; heat resistance